pre algebravvvvvvvvvvvvvvvvvbbbbbbbhhhhhgggffff

## -6(4-t)=12t

# 3 Answers

Hi, Caitlin.

To solve equations like this type, make sure to follow three steps:

1) Simplify both sides of the equation

2) Make sure there is only a variable term (letters) on one side of the equation

3) Think "opposite" - that is, do opposite operations in the opposite order of operations

-6 (4 - t) = 12t

1) The left side is not simplified. We can take care of that by distributing the negative 6 to both members of the ( )'s grouping:

-24 + 6t = 12t

2) We have variable terms on both sides of the equation.

-24 + 6t = 12t

- 6t - 6t

-24 = 6t

3) Now think opposite operation on what's preventing the letter from being alone. The t is being multiplied by 6... so we divide by 6 on both sides:

-24 = 6t

6 6

-4 = t

Or t = -4 to say it "frontwards."

If you are asked to check your answer, put the value of -4 in place of **
t** in the original problem:

-6 (4 - **t**) = 12**t**

-6 (4 - (**-4**)) = 12(**-4**)

-6 (4 + 4) = 12 • -4

-6 • 8 = 12 • -4

-48 = -48

It worked!

So your overall goal is to get t by itself Right?

So, first distribute the -6 : so mulitply -6*4 and -6*-t -24+6t=12t

Now move +6t to the other side so the t's are all on the same side, do this by subtracting 6t from both sides:

-24+6t-6t = 12t-6t. Then simplify:

-24=6t. now let's switch both sides so the t is on the left

6t = -24

now we need to get the t by itself by dividing both sides by 6:

(6t)/is just leaves t because the 6's cancel out and -24/6 is -4

so t=-4